1)y=-x²
ветви вниз, вершина параболы (0; 0)
область значений
2) 2)y=(x-2)²+3
ветви верх, вершина параболы (2;3)
3)y=-(x-7)²-1
ветви вниз, вершина параболы (7; -1)
4)y=x²+6x-1=(x+3)^2-10
ветви верх, вершина параболы (-3; -10)
5)y=-x²+2x=-(x-1)^2+1
ветви вниз,вершина параболы (1;1)
1)y=-x²
ветви вниз, вершина параболы (0; 0)
область значений![E(y)=(-\infty;0]](/tpl/images/0097/5000/e48d1.png)
2) 2)y=(x-2)²+3
ветви верх, вершина параболы (2;3)
область значений![E(y)=[3;\infty)](/tpl/images/0097/5000/7777f.png)
3)y=-(x-7)²-1
ветви вниз, вершина параболы (7; -1)
область значений![E(y)=(-\infty;-1]](/tpl/images/0097/5000/81ea7.png)
4)y=x²+6x-1=(x+3)^2-10
ветви верх, вершина параболы (-3; -10)
область значений![E(y)=[-10; \infty)](/tpl/images/0097/5000/d6876.png)
5)y=-x²+2x=-(x-1)^2+1
ветви вниз,вершина параболы (1;1)
область значений![E(y)=(-\infty;-1]](/tpl/images/0097/5000/81ea7.png)